Code Switching and Code Mixing: An Analysis in Boy William’s Reality Show ‘The Family’ - Callista Buena Sinamo; Utari Praba Astuti; Francisca Maria Ivone (Universitas Cokroaminoto Palopo, 2024)
This study aims to identify and analyze the types of code switching and code mixing between Indonesian and English in Boy William’s speech. The analysis utilizes Macswan's code switching and Musyken's code mixing theories to examine two episodes of 'The Family' reality show on the BW YouTube channel. Direct observation involving transcribing and taking notes on videotaped utterances was applied to analyze code switching and code mixing. The research findings indicated that Intra-sentential code switching was the predominant form of code switching observed in Boy William's speech. He regularly switched languages from English to Indonesian in one sentence to another, and vice versa. Nonetheless, alternation was the predominant form of code mixing that appeared. The phenomena of Indonesian-English in Boy William's speech is recognised as a consequence of conscious choice to embrace a bilingual identity in contemporary life. This study presents an analysis of code switching and code mixing in an Indonesian influencer who comes from a multicultural family. This study is limited to an oriental bilingual participant. Further studies with local Indonesian individuals are necessary to provide a more comprehensive understanding of how the influence of Indonesian-English mixed language impacts the younger generation in Indonesia.